Plasmonic Nanozymes: Leveraging Localized Surface Plasmon Resonance to Boost the Enzyme‐Mimicking Activity of Nanomaterials - Xu, Guopeng; Du, Xuancheng; Wang, Weijie; Qu, Yuanyuan; Liu, Xiangdong; Zhao, Mingwen; Li, Weifeng; Li, Yong‐Qiang (Small (Weinheim an der Bergstrasse, Germany), 2022)
Nanozymes, a type of nanomaterials that function similarly to natural enzymes, receive extensive attention in biomedical fields. However, the widespread applications of nanozymes are greatly plagued by their unsatisfactory enzyme‐mimicking activity. Localized surface plasmon resonance (LSPR), a nanoscale physical phenomenon described as the collective oscillation of surface free electrons in plasmonic nanoparticles under light irradiation, offers a robust universal paradigm to boost the catalytic performance of nanozymes. Plasmonic nanozymes (PNzymes) with elevated enzyme‐mimicking activity by leveraging LSPR, emerge and provide unprecedented opportunities for biocatalysis. In this review, the physical mechanisms behind PNzymes are thoroughly revealed including near‐field enhancement, hot carriers, and the photothermal effect. The rational design and applications of PNzymes in biosensing, cancer therapy, and bacterial infections elimination are systematically introduced. Current challenges and further perspectives of PNzymes are also summarized and discussed to stimulate their clinical translation. It is hoped that this review can attract more researchers to further advance the promising field of PNzymes and open up a new avenue for optimizing the enzyme‐mimicking activity of nanozymes to create superior nanocatalysts for biomedical applications. Plasmonic nanozymes (PNzymes), the “beautiful and incredible” encounter between nanozymes and localized surface plasmon resonance effects, and their catalytic mechanisms, bioapplications as well as current challenges and further perspectives are systematically summarized and discussed. It is anticipated that this review will provide new insights into the design of powerful nanocatalysts for biomedical applications.